Active solution heating and cooling in electrospinning enabling spinnability from various solvents - Abbas, Dunia; Mu'Min, Muhammad S.; Bonanno, Marco; Thiele, Simon; Boehm, Thomas (Journal of Applied Polymer Science, 2022)
Solution electrospinning is a facile method for the production of nanofibrous meshes. Here, we present a syringe-jacket heat exchanger as a simple add-on for solution electrospinning, which enables spinning from various solvents by a direct and precise solution temperature control between -20 degrees C and 100 degrees C. An effective manipulation of the solvent evaporation rate is enabled by adjusting the temperature. Exemplarily, we investigated the spinning of poly(vinylidene fluoride)-co-hexafluoropropylene (PVDF-HFP) in pure dimethylacetamide (DMAc) or acetone as representatives of low and highly volatile solvents. Electrospinning of these solutions is not possible at ambient conditions, either due to a too low or too high evaporation rate. However, we find that PVDF-HFP nanofibers can be successfully electrospun from DMAc at a solution temperature of 75 degrees C and from acetone at -19 degrees C. We show for the first time the use of an active solution cooling for electrospinning from a highly volatile solvent such as acetone. The ability to precisely adjust the solution temperature during electrospinning offers an improved process control and broadens the spectrum of spinnable solution compositions. Especially the prospect of replacing highly toxic solvents with less-toxic solvents such as acetone opens up a wide field of application for the produced fibers.
CRIS-Team WoS Importer:2022-06-24